Церковнocлавянский Недельный октoих как функциональная разновидность Общей минеи - Юрьевич Темчин, Сергей (Slavistica Vilnensis, 2003)
The Old Church Slavonic weekly octoechos contains 7 daily services (designed for each day of the week from Sunday through Saturday), usually of different octoechos modes.The author argues that despite its name, this type of octoechos was used in the immovable (calendarian) cycle of the ecclesiastical year as a functional equivalent of the general menaion. This argument is rooted in the fact that in the Orthodox tradition, each day of the week has its own symbolic meaning: Sunday was dedicated to the Lord, Monday to the angels, Thursday to John the Baptist, Wednesday to the Virgin, Thursday to the Apostles, Friday to the Cross, and Saturday to all the saints and all the dead. Thus, the single Sunday service of the weekly octoechos could be used during every immovable Lord’s Day (i.e., holiday commemorating an event in the life of Jesus, such as Christmas), the single Wednesday service could be used for every immovable Day of the Virgin (i.e., holiday commemorating an event in the life of the Virgin Mary, such as the Dormition), etc.